Lepota Poroka . The Beauty of the Sin - Nikolić, Živko (Central Film Beograd, 1986)
This film drama opens with a portrayal of the way of life in the remote Montenegrin mountain village, almost untouched by modern civilization. People there still follow strict and Draconian archaic codes which instruct a husband to kill his wife with a hammer over a loaf of bread if she is proven unfaithful. In this environment, a young married couple apparently lives harmoniously, but in poverty. They accept an invitation from their friend who has left for the sea coast in search of money and follow his example. While the husband manages to get a job in a salt factory, she starts working as a cleaning lady in a nudist camp. They are both shocked by the reality of the modern way of life although the hundreds of naked bodies they see and the atmosphere of joie de vivre make them slowly question their rigid norms. Traditionally brought up, the wife is initially terrified of nudity, but under the influence of two young foreigners whose apartment she is cleaning, she starts freeing her chained sensuality. The tragic outcome resolves this dilemma between the beauty of sin or the ugliness of virtue.